Faktor Resiko Gejala Infeksi Saluran Pernafasan Akut (ISPA) Pada Balita Di Puskesmas Depati VII Kabupaten Kerinci : Risk Factors for Symptoms of Acute Respiratory Infection (ARI) in Toddlers at the Depati VII Public Health Center, Kerinci Regency - Nabila, Weni Seprilia; Sari, Rumita Ena; Hidayati, Fajrina (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2022)
Acute Respiratory Infection (ARI) was one type of environmental-based infectious disease. In Indonesia, ARI always occupies the first position of 10 cases of disease with the highest number. The results of Riskesdas 2018 reported that the prevalence of ARI was 9.3%. This study aims to determine the factors associated with ARI symptoms in children under five in the Depati VII Public Health Center of Kerinci Regency in 2022. This study was a quantitative study with a cross sectional design. The sampling technique used accidental sampling technique with a total of 85 samples. Data collection was carried out in February-March 2022. The data analysis technique used the chi-square test. The results showed that the factors related to the symptoms of ARI in toddlers were the area of ​​ventilation with ARI symptoms in toddlers (p=0.025), humidity levels in toddlers (p=0.001), occupancy density (p=0.017), smoking habits (p=0.002) while the unrelated were immunization status (p=0.491) and exclusive breastfeeding (p=0.402). The area of ​​ventilation, the level of humidity, the level of occupancy density, and smoking habits have a relationship with the symptoms of ARI in children under five. It is hoped that health workers will improve the early warning system for ARI outbreaks by increasing knowledge, attitudes and behavior about the importance of healthy home hygiene, and health centers can also work with religious leaders/communities to maintain environmental health, especially healthy homes through socialization.